Exact Solutions to Extended Nonlinear Schrodinger Equation in Monomode Optical Fiber - BAI Cheng-Lin ZHAO Hong Wang Wei-Tao (Communications in theoretical physics, 2006)
By using the generally projective Riccati equation method, more new exact travelling wave solutions to extended nonlinear Schrodinger equation （NLSE）, which describes the femtosecond pulse propagation in monomode optical fiber, are found, which include bright soliton solution, dark soliton solution, new solitary waves, periodic solutions, and rational solutions. The finding of abundant solution structures for extended NLSE helps to study the movement rule of femtosecond pulse propagation in monomode optical fiber.